Nitrogen Isotopes Suggest Sex‐Based Diet Differences on the Breeding Grounds for a Sexually Monomorphic Migratory Passerine - Autumn R. Iverson; Renée L. Cormier; Diana L. Humple; Thomas P. Hahn; Jessica Schaefer; Elisha M. Hull; Walter H. Sakai; Samuelle Simard‐Provençal (Ecology and Evolution, 2025)
ABSTRACT Differential foraging by sex can have important implications for understanding the ecology of a species. This can be especially difficult to study through observations alone in sexually monomorphic species, such as the Golden‐crowned Sparrow (Zonotrichia atricapilla), and for species in remote areas. We used nitrogen and carbon stable isotope analysis to determine the relative trophic position between the sexes for 73 individual Golden‐crowned Sparrows, a migrant songbird species with little known diet information from remote breeding locations of Alaska and northwestern Canada. We found no evidence of differences in feather δ13C between the sexes suggesting similar habitat use, but we found an average 0.3‰ increase each year that may indicate increasingly water stressed habitats. We found that females had significantly higher values of feather δ15N (mean 5.4‰; mean for males 4.5‰) after accounting for year and feather collection location and in a subset of GPS‐tagged birds with known breeding locations, after accounting for year, breeding latitude, elevation, and distance to shoreline. We infer that females may be foraging on more food items from a higher trophic level than males on breeding grounds, which may reflect a physiological need to replace lost nutrients from nesting. If females rely on insects during the breeding season, then their success will be tied to insect populations which are generally experiencing large declines. Additionally, we provide mass and wing chord measurements from genetically sexed individuals to add to currently low published sample sizes for this monomorphic species.